2010
DOI: 10.2147/vhrm.s6795
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in stroke: a review of SPARCL and subgroup analysis

Abstract: Abstract:Statin therapy in patients with cardiovascular disease is associated with reduced incidence of stroke. The Stroke Prevention by Aggressive Reduction of Cholesterol Levels (SPARCL) trial showed daily treatment with 80 mg of atorvastatin in patients with a recent stroke or transient ischemic attack (TIA) reduced the incidence of fatal or nonfatal stroke by 16%. Several post hoc analyses of different subgroups followed the SPARCL study. They have not revealed any significant differences when patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Giving folic acid and B vitamins helps reduce homocysteine levels, which are currently known risk factors for stroke [7]. Simvastatin was also administered to this patient following the SPARCL trial, which discovered the benefts of statin therapy in lowering the risk of stroke [8]. Because hypertension is the most severe risk factor, blood pressure must be maintained in every stroke patient who has hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Giving folic acid and B vitamins helps reduce homocysteine levels, which are currently known risk factors for stroke [7]. Simvastatin was also administered to this patient following the SPARCL trial, which discovered the benefts of statin therapy in lowering the risk of stroke [8]. Because hypertension is the most severe risk factor, blood pressure must be maintained in every stroke patient who has hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These results may serve as a practical reflection of prior randomized controlled trials and several observational analyses which highlight the statin associated risk reduction of stroke. 4,21,22…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed patients with postischemic-stroke treatment with atorvastatin showed improving neurological recovery [ 105 ]. However, this beneficial effect is partly counteracted by an increased risk of hemorrhagic stroke [ 106 ]. Moreover, atorvastatin induced intracranial hemorrhages in wildtype fish [ 107 ] and induced cerebral hemorrhage in a zebrafish model ( Figure 8 ), which offers an opportunity to screen cerebrovascular-protective compounds.…”
Section: Cerebral Hemorrhage Modelmentioning
confidence: 99%